Beyond the Educational Context: Relevance of Intrinsic Reading Motivation During COVID-19 Confinement in Spain - De Sixte, Raquel; Fajardo, Inmaculada; Mañá, Amelia; Jáñez, Álvaro; Ramos, Marta; García-Serrano, María; Natalizi, Federica; Arfé, Barbara; Rosales, Javier (Frontiers in Psychology, 2021)
What role could have intrinsic motivation towards reading in an extraordinary situation like the recent confinement? This research examines the relationship between intrinsic reading motivation (IRM) and reading habits in an adult population considering types of reading (for leisure, for work/study, social networks, and news), gender, and distress generated by the COVID-19 pandemic. Participants were 3849 adults from Spain who were surveyed about their reading practices: before, during the first weeks and after several weeks of confinement. Linear mixed effects models (LMM) were used to analyze the data. Results showed a three-way interaction between reading frequency, IRM and type of reading. Also, distress seems to pose a differential impact depending on type of reading. The higher the IRM the lesser the time devoted to study/work reading and the more to social and news reading (at the beginning of confinement). In this sense, IRM can function as a protective factor of reading behavior but only for leisure reading. Results support previous findings about the importance to consciously promote this type of motivation in all individuals beyond educational contexts since it seems to be positively related to well-being. Other results and implications are discussed.